ANALISIS KEBUTUHAN MODEL SITUATIONAL JUDGMENT TEST DALAM UJI KOMPETENSI CALON KEPALA SEKOLAH - Yogi Satrio Aribowo; Tity Kusrina; Dewi Amaliah Nafiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Test (SJT) in the competency assessment of prospective school principals as an alternative to the conventional methods still predominantly used in Indonesia. The main issue addressed is the lack of assessment instruments capable of evaluating contextual competencies, which are crucial in the school leadership role. A descriptive qualitative approach was employed, with data collected through semi-structured interviews and questionnaires involving key educational stakeholders in Pemalang Regency. The results show that a majority of respondents (60% stated